Designing the coal preparation plant of the future - Arnold, Barbara J.; Klima, Mark S.; Bethell, Peter J. (Society for Mining, Metallurgy, and Exploration, 2007)
Most books on coal preparation focus on theory or day-to-day issues and operations. Designing the Coal Preparation Plant of the Future provides a unique, thought-provoking look at the industry from a different point of view-that of the preparation plant designer or engineer. How can we design more effective plants and what will plants look like in the future? What are the new techniques for designing plant layouts, monitoring performance, and building in preventive maintenance? What challenges face the industry and how can operators capitalize on opportunities to maximize yield, reduce costs,